4x+9-67(x+1)=6x+7

Simple and best practice solution for 4x+9-67(x+1)=6x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+9-67(x+1)=6x+7 equation:


Simplifying
4x + 9 + -67(x + 1) = 6x + 7

Reorder the terms:
4x + 9 + -67(1 + x) = 6x + 7
4x + 9 + (1 * -67 + x * -67) = 6x + 7
4x + 9 + (-67 + -67x) = 6x + 7

Reorder the terms:
9 + -67 + 4x + -67x = 6x + 7

Combine like terms: 9 + -67 = -58
-58 + 4x + -67x = 6x + 7

Combine like terms: 4x + -67x = -63x
-58 + -63x = 6x + 7

Reorder the terms:
-58 + -63x = 7 + 6x

Solving
-58 + -63x = 7 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-58 + -63x + -6x = 7 + 6x + -6x

Combine like terms: -63x + -6x = -69x
-58 + -69x = 7 + 6x + -6x

Combine like terms: 6x + -6x = 0
-58 + -69x = 7 + 0
-58 + -69x = 7

Add '58' to each side of the equation.
-58 + 58 + -69x = 7 + 58

Combine like terms: -58 + 58 = 0
0 + -69x = 7 + 58
-69x = 7 + 58

Combine like terms: 7 + 58 = 65
-69x = 65

Divide each side by '-69'.
x = -0.9420289855

Simplifying
x = -0.9420289855

See similar equations:

| x^3+3x^2-81x-85=0 | | -(7y+5)-(-6y-8)=0 | | (4/10x)-2x+(8/5)=(4/5) | | x/2-4=x/5-1 | | 87*28/29*4/9 | | 9x+21+x=5+x+5 | | 12+5n=62 | | -3(6x-5)+3=18x+18 | | 5y+8=48 | | 8x+3=8(x+7) | | 11/7=X/6 | | (2-3x)*(2-3x)=8 | | 0.14(y-3)+0.06y=0.10y-0.5 | | 9x+13=5x+89 | | x+18+21x=3x+9 | | x+28+21x=3x+9 | | 16(18m-4)=24m+8 | | 216-3x=42x+16 | | 0.18(y-5)+0.20=0.08y-1.8 | | (2-3x)X(2-3x)=8 | | 7(3x+5)=-(x+9) | | 3(x-5)+4x=0 | | 5/6x-1/2=7 | | 7+19z-2=8z+21-5z | | 16(18m+-4)=m+8 | | 4/7x+6/7=-6/7 | | 15/2x+19=12x+7/2 | | 4/7x6/7=-6/7 | | 4x/8+16/2x | | 2/3+1/2t=3 | | 5670(1+0.035/2)^2 | | 16(18m-4)=m+8 |

Equations solver categories